Social mobility and fertility - Gianpiero Dalla Zuanna (Demographic Research, 2007)
Intra- and inter-generational social mobility have in the past played an important role in attempts to explain fertility behaviour, and continue to do so today. The opinions expressed by social scientists in the first part of the 20th century are renewed and confirmed. More specifically: (1) intra-generational social mobility has been reinforced by the personal well-being aspirations and job careers of women; (2) status anxiety parents feel for their children pushes fertility down in large areas of the developed world (mainly in southern European and eastern Asian countries). Therefore, the provocative idea of AriÃƒÂ¨s that in the rich world, the child-king has now been replaced by the couple-queen does not perfectly hold.